Safety, reliability and accuracy of small renal tumour biopsies: results from a multi‐institution registry. (7th September 2016) - Richard, Patrick O.; Jewett, Michael A. S.; Tanguay, Simon; Saarela, Olli; Liu, Zhihui Amy; Pouliot, Frédéric; Kapoor, Anil; Rendon, Ricardo; Finelli, Antonio
Abstract : Objective: To validate, in a multi‐institution review, the safety, accuracy and reliability of renal tumour biopsy (RTB) and its role in decreasing unnecessary treatment. Materials and Methods: We conducted a multi‐institution retrospective study of patients who underwent RTB to characterize a small renal mass (SRM) between 2011 and May 2015. Patients were identified using the prospectively maintained Canadian Kidney Cancer information system. Diagnostic and concordance rates were presented using proportions, whereas factors associated with a diagnostic RTB were identified using a logistic regression model. Results: Of the 373 biopsied SRMs, the initial biopsy was diagnostic in 87% of cases. Of the 47 non‐diagnostic biopsies, 15 had a repeat biopsy of which, 80% were diagnostic. When both were combined, therefore, a diagnosis was obtained in 91% of SRMs. Of these, 18% were benign. Size was the only factor found to be associated with achieving a diagnostic biopsy. RTB histology and nuclear grade (high or low) were found to be highly concordant with surgical pathology (86 and 81%, respectively). Of the discordant tumours ( n = 16), all were upgraded from low to high grade on surgical pathology. Adverse events were rare (<1% of cases). Conclusion: The present multi‐institution study confirms that RTB of SRMs is safe, accurate and reliable across institutions, while decreasing unnecessary treatment. Given our findings, RTBs may be a helpful tool with which to triage SRMs and guide appropriate management.